Creep Properties and Constitutive Model of Salt Rock - Qiang Zhang; Zhanping Song; Junbao Wang; Yuwei Zhang; Tong Wang (Advances in Civil Engineering)
Due to the advantages of low porosity, low permeability, high ductility, and excellent capacities for creep and damage self-healing, salt rock is internationally considered as the ideal medium for underground storage of energy and disposal of radioactive waste. As one of the most important mechanical properties of salt rock, creep properties are closely related to the long-term operation stability and safety of salt rock underground storage cavern. A comprehensive review on the creep properties and constitutive model of salt rock is put forward in this paper. The opinions and suggestions on the research priority and direction of salt rock's mechanical properties in the future are put forward: (1) permeability variation of salt rock under the coupling effect of temperature and stress; (2) damage mechanism and evolution process under the effect of creep-fatigue interaction and low frequency cyclic loading; (3) microdeformation mechanisms of salt rock and the relationship between microstructure variations and macrocreep behavior during creep process; (4) the establishment of the creep damage constitutive model with simple form, less parameters, easy application, and considering the damage self-healing ability of salt rock simultaneously.